Work–Family Conflict’s Association With the Work Attitudes of Job Involvement, Job Satisfaction, and Organizational Commitment Among Southern Prison Staff - Lambert, Eric G. (Criminal justice policy review, 2021)
Prisons depend on their employees, and staffing a prison is expensive. Approximately 80% of a prison’s budget is for staff wages and benefits. Prisons are not generally viewed as desirable places to work, thus recruiting and retaining correctional officers can be difficult. Work-related stress can negatively affect staff members’ home lives, and home stress can make an employee distracted and endangered at work. Time-, strain-, behavior-, and family-based work–family conflicts were hypothesized to impact three work attitudes (job involvement, job satisfaction, and organizational commitment) negatively. Time-based conflict had no significant effects on any of the work attitudes. Strain-based conflict had significant negative effects on job satisfaction and organizational commitment but not job involvement. Behavior-based conflict had significant negative effects on all three work attitudes. Contrary to our hypotheses, family-based conflict had significant positive effects on all three. Work–family conflict is a significant work attitude-associated stressor for correctional staff; therefore, policy recommendations to address it are made.